Pelarutan Emas pada Pelindian Konsentrat Emas Hasil Roasting Menggunakan Reagen Tiosianat - Fika Rofiek Mufakhir; J M Sinaga; Soesaptri Oediyani; Widi Astuti (Jurnal Rekayasa Proses, 2019)
A B S T R A C TDissolution of gold from roasting concentrate of gold ore using potassium thiocyanate with the presence of ferric chloride as an oxidizer was investigated. The concentrate was taken from Lengkukai gold mine. Gold ore particles under 53 µm in size were roasted at varied temperature, separated using wet magnetic separator, and finally leached. The X-ray diffraction (XRD) analysis showed that there were phase changes after roasting with the emergence of new phases such as hematite, pyrrhotite, and almandine. Leaching of gold concentrate after roasting and magnetic separation showed that gold was in non-magnetic concentrate at 950oC with the highest gold dissolution of 0.95 mg/L, while magnet concentrate was completely absent. Experiments with the addition of Fe3+ ion oxidizers for 24-hour range did not have significant effect on gold dissolution. The highest gold concentration obtained of 2.29 mg/L was obtained at 12 hours with 0.1 M FeCl3. The increase of thiocyanate reagent concentrations, which showed a linear correlation to gold dissolution, produced up to 2.25 mg/L of gold concentration (12 hours at 0.3 M KSCN).Keywords: ferric ion gold dissolution; gold concentrate; roasting; thiocyanate A B S T R A KPelarutan emas dari konsentrat hasil roasting bijih emas tambang Lengkukai menggunakan reagen pelindi kalium tiosianat dengan penambahan ferric chloride sebagai oksidator telah diteliti. Partikel bijih emas dengan ukuran di bawah 53 µm di-roasting pada berbagai temperatur kemudian dipisahkan menggunakan pemisah magnetik basah dan akhirnya dilindi. Hasil analisis X-ray diffraction (XRD) menunjukkan adanya perubahan fase setelah roasting dengan munculnya fase-fase baru yaitu hematit, pirohitit dan almandin. Pelindian konsentrat emas hasil roasting dan pemisahan magnetik menunjukan emas berada pada konsentrat non magnet temperatur roasting 950 oC dengan pelarutan emas paling tinggi sebesar 0,95 mg/L, berbeda dengan konsentrat magnet yang sama sekali tidak ada. Percobaan dengan penambahan oksidator ion Fe3+ selama rentang 24 jam tidak memberikan efek yang signifikan terhadap pelarutan emas. Dari penelitian ini didapatkan konsentrasi emas tertinggi sebesar 2,29 mg/L pada 12 jam dengan konsentrasi FeCl3 0,1 M. Sedangkan penambahan konsentrasi reagen tiosianat, yang menunjukan hubungan linier terhadap pelarutan emas, menghasilkan konsentrasi besar hingga 2,25 mg/L selama 12 jam pada konsentrasi KSCN 0,3 M.Kata kunci: ion besi III; konsentrat emas; pelarutan emas; roasting; tiosianat